The Force Publique's campaigns in the Congo-Arab War, 1892-1894. (29th July 2019) - Draper, Mario
ABSTRACT: Between 1892 and 1894 the Force Publique of King Leopold II's Congo Free State engaged in a series of little-known counter-insurgency operations against ivory and slave traders from Zanzibar, commonly referred to as Arabs. Without a particularly strong tradition of imperial service, this article argues that the predominantly Belgian officer corps borrowed and adapted methods used by more experienced colonial forces in the 19 th Century. Whether taken from existing literature or learned through experience, it reveals that the Force Publique 's counter-insurgency methods reflected many of the more recognisable aspects of traditional French and British approaches. It suggests that, despite the unique nature of each colonial campaign, basic principles could be adapted by whomsoever to overcome the military and political challenges of colonial conquest. The Force Publique 's campaigns in the Congo-Arab War, therefore, provide further evidence as to how some base theories could be universally applied.